Resilience of Single Mother Low Economic Levels who Have Children Aged 6-12 with During the Covid-19 Pandemic - Yulianti, Natalia Ratna; Dwi Nugraheni, Tania; Gayatina, Andri Kenti (Holistic Nursing Plus, 2023)
Background: The COVID-19 pandemic has had an impact in various fields. Parents have been affected by the COVID-19 pandemic, especially single mothers. The challenge for single mothers who have children aged 6-12 years during the COVID-19 pandemic is accompanying children to study at home. Single mothers who are not used to accompanying children to study will cause a burden. The pressure experienced cannot be tolerated, because single mothers must rise in order to survive and adapt. Previous studies have shown a very good picture of the resilience of a single mother because it reaches a stage that corresponds to the aspect of resilience. Other studies have found that parents who accompany school children at home during the COVID-19 pandemic have low resilience. However, a study on single mothers with low economic levels who have children aged 6-12 years during the COVID-19 pandemic has never been done. Purpose: The purpose of this study was to explore the resilience of single mothers with low economic levels who have children aged 6-12 years during the COVID-19 pandemic. Methods: This research is qualitative research with a phenomenological study approach. The research location is in a district in city of Salatiga, Indonesia. Participants were five single mothers who were selected using a purposive sampling technique with inclusion criteria having children aged 6-12 years with low economic levels during the COVID-19 pandemic. Data is collected by conducting in-depth interviews. The data were analyzed using the Colaizzi method. Results: The results of the research resulted in six themes, namely 1) Mother received support from siblings and biological family; 2) Mother had to work hard to make a living; 3) Relieved in accepting the situation; 4) Mother's independence to live life; 5) Mother's patience to control anger; 6) Mother came, prayed and thanked God Conclusions: Single mothers who have children with low economic levels aged 6-12 years had resilience during the COVID-19 pandemic.